2022
DOI: 10.1107/s2052252522002147
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of Cu Kβ radiation for the single-crystal X-ray structure determination of crystalline sponges

Abstract: The crystalline sponge method facilitates the X-ray structure determination of samples that do not crystallize or are too sparsely available to afford viable crystallization. By including these materials in a metal–organic framework, the structure of the guest molecules can be determined. Some of the inherent difficulties of this method are discussed and the use of Cu Kβ radiation is presented as a simple and effective means to improve the quality of the diffraction data that can be obtained from a sponge crys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Although the CS method has added another tool to the arsenal of advanced crystallization methods, uptake has been limited to a handful of laboratories globally (Metherall et al, 2023). Significant proportions of work undertaken on CS analysis have been devoted to method development, including more efficient synthesis of host crystals, optimization of hardware and improvements to guest exchange strategies for reactive guests (Waldhart et al, 2016;Meurer et al, 2022;Sakurai et al, 2017). This branch of research has also examined the reliability of host-guest interactions to improve our understanding of analyte and host behaviours (Hayes et al, 2016;Carroll et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although the CS method has added another tool to the arsenal of advanced crystallization methods, uptake has been limited to a handful of laboratories globally (Metherall et al, 2023). Significant proportions of work undertaken on CS analysis have been devoted to method development, including more efficient synthesis of host crystals, optimization of hardware and improvements to guest exchange strategies for reactive guests (Waldhart et al, 2016;Meurer et al, 2022;Sakurai et al, 2017). This branch of research has also examined the reliability of host-guest interactions to improve our understanding of analyte and host behaviours (Hayes et al, 2016;Carroll et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, only shortly afterwards it was reported that using monochromatic X-ray radiation was beneficial for the interpretability of structures (Bragg & Bragg, 1913). For singlecrystal X-ray diffraction, this has held until today, and the latest and most consequential contribution to this development with in-house instrumentation is the recent report of using copper K (Meurer et al, 2022) to avoid even the K 1 -K 2 splitting for the employed X-ray radiation. Sometimes instrumentation has led to unexpected contamination, leading to lower monochromaticity, such as the reported contamination by a higher harmonic of the monochromator, i.e.…”
Section: Introductionmentioning
confidence: 99%